Informal Health Care Service Provider: A Health Protection Challenge for Developing Countries - Rafia Rahman (Issues and Development in Health Research Vol. 4, 2021)
75 countries had less than 2.5 health workers per 1000 people.Countries with less than 2.28 doctors, nurses, and midwives per 1000 people failed to fulfil the aim of 80 percent skilled birth attendance and child immunisation, according to the World Health Report. Due to the lack, patients, particularly the poor and disadvantaged, have been forced to seek health care from the informal sector as they are more socially and community focused Appropriate formal health workforce is required to build an effective, efficient, and equitable health system that improves population health. There is a scarcity and a crisis of it. Healthcare-seeking is not a simple human behavioral nature. The combined efforts of the public and private sectors nearly impossible to produce the required formal health workforce. Transform unregistered health care service providers (HCSP) into government-registered, well-trained HCSP. It would be able to prevent malpractice, ensure standard treatment, and hold people accountable for referral responsibility. Both primary and secondary data were collected. A face-to-face interview and a focus group discussion were conducted. People who are illiterate (no education) as well as literate (completed primary school to a higher level of education) seek out informal healthcare providers. Households with incomes ranging from 10,000 to 30,000 were classified as low, middle, and upper middle, with people aged zero to sixty having the option of receiving health services from a traditional healer (kobiraj), homoeopathy, RMP, and drug seller.